SIMULAÇÃO SINTÉTICA DO EFEITO DO METABISSULFITO DE SÓDIO NO DESPRENDIMENTO DO OXIGÊNIO DISSOLVIDO EM ÁGUAS - Jeronimo, Carlos Enrique; Fernandes, Hermano Gomes; Sousa, Joao Fernandes; Marques, Marcelo Fidelis Mendes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704987 In shrimp culture, sodium metabissulfite is used for the preservation after the harvest. However, largeparts are discarded in an irregular manner directly to mangrove swamps and other receptorsbiotopes. Amongst others, this substance acts by provoking desorption of oxygen, leading to severedamage of the ecosystem. We developed an experimental method to study desorption andconsumption kinetics of dissolved oxygen using oxygen saturated distilled water as a reference formaximum saturation. The influence of sodium metabissulfite concentration and temperature wereexamined. Monitoring was accomplished by a digital oxymeter. Our results were adjusted to a firstorderrate law to obtain the rates of oxygen desorption under the given conditions (yielding heat forthe deoxygenating system in question as 11.39 kJ/mol). These results should contribute to widen the knowledge of ambiental factors envolved in shrimp culture and should provide evidence for theeffects caused in nature by the given contaminations.